디젤 및 가솔린자동차 배출원의 구성물질 성분비 개발에 관한 연구 - 강병욱; 이승복; 배귀남; 임철수; 나광삼; 이학성; 조민식 (한국대기환경학회, 2010)
The purpose of this study was to develop the PM2.5 source profiles for diesel and gasoline-powered vehicles,which contained mass abundances in terms of mass fraction of PM2.5 of chemical species. Seven diesel-powered vehicles and nine gasoline-powered vehicles were sampled from a chassis dynamometer exhaust dilution system. The species measured were water-soluble ions, elements, elemental carbon (EC), and organic carbon (OC). From this study, the large abundances of EC (54.5%), OC (26.0%), SO42- (1.5%), NO3- (0.8%), and S (0.6%) were observed from the diesel-powered vehicle exhaust showing that carbons were dominant species. The gasolinepowered vehicle exhaust emitted large abundances of OC (38.3%), EC (4.2%), SO42- (3.6%), NH4+ (3.5%), and NO3- (3.0%). The abundances of SO42-, NH4+, and NO3- from gasoline vehicle were greater than those of diesel vehicle. The emissions of P, S, Ca, Fe, and Zn among trace elements for the gasoline vehicle were greater than 1%of the PM2.5 mass unlike those for the diesel vehicle. Particularly, the fraction of Zn was five times higher from the gasoline vehicle than that from the diesel vehicle. The source profiles developed in this work were intensively examined by applying chemical mass balance model.